Technology, demand, and productivity: What an industry model tells us about business cycles - Zuzana Molnárová; Michael Reiter (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2021)
In this paper, we study the relative importance of demand and technology shocks in generating business cycle fluctuations, both at the aggregate level and at the level of individual industries. We construct a New Keynesian DSGE model that is highly disaggregated at the industry level with an input-output network structure. Measured productivity in the model fluctuates in response to both technology and demand shocks due to endogenous factor utilization. We estimate the model by the simulated method of moments using U.S. industry data from 1960 to 2005. We find that the aggregate technology shock has zero variance. Exogenous shocks to technology are necessary for our model to fit the data, but these shocks are exclusively industry-specific, uncorrelated across industries. The bulk of the aggregate fluctuations, including those in aggregate measured productivity, are explained through shocks to aggregate demand. This shock structure is supported by a host of information from the disaggregate data. Our second finding is that about half of the decrease in the cyclicality of measured productivity in the U.S. after the mid-1980s can be explained by the reduction in the size of demand shocks, in line with the narrative of the great moderation.
Keywords: E32; E24; E37; 330; business cycles; productivity; industries; factor utilization; input-output linkages; networks